Bone Microarchitecture Changes in Peri- and Post-Menopausal Women: Cortical Porosity is a Marker for Accelerated Change During Menopause - Bhatla, Jennifer L.; Burt, Lauren A.; Hanley, David A; Boyd, Steven K (CMBES Proceedings, 2016)
During menopause, accelerated bone loss occurs, accompanied by bone microarchitecture changes. This has primarily been characterized with cross sectional dual x-ray absorptiometry (DXA). Our longitudinal study aims to compare rate of change (ROC) in bone microarchitectural parameters in peri- and post-menopausal women using high resolution peripheral quantitative computed tomography (HR-pQCT). Participants were selected from the Calgary Canadian Multicentre Osteoporosis Study (CaMos) from menopause information provided by questionnaire (stage 1-5). The peri-menopause group (n=26) includes women beginning menopause transition to nearing the end (stage 2-4). The post-menopause group (n=65) had completed the midlife process (stage 5). HR-pQCT (Scanco Medical, Switzerland) non-dominant radius and left tibia scans provided baseline and follow-up (average=5.5yrs) assessments of bone mineral density, total area (Tt.Ar) and cortical porosity (Ct.Po). To compare repeat scans, automated 3D image registration was conducted (IPL software). T-tests compared differences between groups. Both groups lost radius and tibia bone density. ROC between groups was not different at the radius. In contrast, tibia Tt.Ar and Ct.Po ROC differed. Peri-menopausal women experienced accelerated Ct.Po change compared to post-menopausal women (9.0 and 6.3%/yr respectively, p=0.046) and less Tt.Ar change (0.06 and 0.13%/yr, p=0.017). Increased ROC in Ct.Po observed in peri-menopausal women is consistent with data showing increased bone remodeling during menopause, with inadequate repair. Similarly, Tt.Ar is known to increase with age, as observed in both groups, but appears to occur at a faster rate post-menopause. This is the first longitudinal study at high resolution to investigate longitudinal microarchitecture changes during and after menopause.